Adipocyte Hypertrophy, Fatty Liver and Metabolic Risk Factors in South Asians: The Molecular Study of Health and Risk in Ethnic Groups (mol-SHARE) - Anand, Sonia S. (Public Library of Science, 2011)
OBJECTIVE: We sought to determine if differences in the distribution and characteristics of adipose tissue between South Asians and white Caucasians account for differences in risk factors for cardiovascular disease. RESEARCH DESIGN AND METHODS: We recruited 108 healthy South Asians (36.8 years) and white Caucasians (34.2 years) within three BMI strata. Body composition, adipocyte size, abdominal fat area, and hepatic adiposity were assessed and related to fasting glucose, insulin, lipids and adiponectin. RESULTS: After adjustment for age, sex, and BMI, South Asians compared to white Caucasians had higher ln fasting insulin (mean difference (md): 0.44; 95% CI: 0.20–0.69), lower HDL cholesterol (md: −0.13; 95% CI:−0.26 to −0.01), and lower adiponectin (md: −2.38; 95% CI: −3.59 to −1.17). South Asians also had more body fat (md: 2.69; 95% CI: 0.70 to 4.69), lower lean muscle mass (md: −3.25; 95%CI: −5.35 to −1.14), increased waist to hip ratio (md: 0.03; 95% CI: 0.01–0.05), less superficial subcutaneous abdominal adipose tissue (md: −2.94; 95% CI: −5.56 to−0.32), more deep/visceral to superficial adipose tissue ratio (md 0.34; 95% CI: 0.02 to 0.65), and more liver fat (md: 7.43%; 95% CI: 2.30 to 12.55%). Adipocyte area was increased in South Asians compared to white Caucasians (md: 64.26; 95% CI: 24.3 to 104.1) units(2). Adjustment for adipocyte area attenuated the ethnic differences in insulin (md: 0.22; 95% CI: −0.07 to 0.51), HDL (md: −0.01; 95% CI: −0.16 to 0.13) and adiponectin (md: −1.11; 95% CI: −2.61 to 0.39). Adjustment for differences in adipocyte area and fat distribution attenuated the ethnic difference in liver fat (md: 5.19; 95% CI: 0.31 to 10.06). CONCLUSION: South Asians have an increased adipocyte area compared to white Caucasians. This difference accounts for the ethnic differences in insulin, HDL cholesterol, adiponectin, and ectopic fat deposition in the liver.